Estudo químico dos fungos Stachybotrys levispora e Curvularia inaequalis: uso da rede molecular para a identificação de novos metabólitos - Ribeiro, Alany Ingrid (Universidade Federal de São Carlos, 2019)
Saprobic fungus are being used as an alternative strategy to reduce the use of pesticides harmful to the environment. These microorganisms produce substances capable of inhibiting pathogens that affect agriculture. The structural and chemical diversity of metabolites from microorganism, are factors that call attention mainly to the activity, complexity and numerous stereogenic centers. Alterations in the culture medium, and / or the use of chemical and epigenetic modulators, can activated the silenced routes, giving rise to classes of different compounds from those produced by the main biosynthetic pathway. Analytical tools such as liquid chromatography coupled to high resolution mass spectrometry (LC-HRMS-MS) associated with specific platform for Natural Products, GNPS (Global Natural Product Social Molecular Networking), to facilitate the tracking of analogs of structures with activity described in the literature. In this context, the Saprobic fungi Stachybotrys levisporous (STA) and Curvularia inaequalis (CUI) were selected in previous studies by the SISBIOTA- Bioprospection of saprobic fungi in the PPBIO to be studied from a metabolic point of view. The main objective of this work was to evaluate changes on the chemical profile of these fungus applying the strategy of modification of culture medium in order to identify and / or isolate metabolites produced by the modifications in the supplementation, using analytical tools of isolation and molecular identification networking. Metabolic dereplication studies in STA allowed the identification of of stachybotrylactamas, with stereochemistry different from those in the literature, and facilitating the bioguided isolation of novel substances pertaining to the class of 10-benzo--lactama-5,8,9,10-drimanes. The studies in CUI, was possible to develop a rapid method of isolating metabolites of the classes of chromenes (anofinic and 3,4-trans dihydroxyanofinic acids), amino acids (5-oxoproline) and phytohormone (abscisic acid), with potential antifungal activity described in literature
Chemical study of fungus Stachybotrys levispora and Curvularia inaqualis: the use of molecular network to identify novel metabolites
Keywords: Stachybotrys levispora; GNPS; Molecular networking; Fenilspirodrimanas; Stachybotrys levisporous; GNPS; Global Natural Product Social Molecular Networking; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS